Rancang Bangun Aplikasi Web Penjualan Produk : Studi Kasus pada Bisnis HE Wood Iron - Abdah Maghfuroh; Tarsinah Sumarni (Melati Institute, 2023)
HE Wood Iron is currently facing obstacles in the preparation and execution of sales which are still done manually. This leads to a lack of time, errors in data collection, and poor customer accessibility. To overcome these problems, the author conducted research to propose the implementation of an effective, efficient and secure web-based product sales application. This sales application is made with the PHP programming language and is made based on the website. The system development method used is the waterfall method with an object-oriented approach and the Unified Modeling Language (UML) application development tool. This web-based product sales application facilitates customer transactions, increases administrative efficiency, increases transparency and expands sales coverage through accessibility and digital marketing.